2002
DOI: 10.1103/physrevc.65.034602
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-range correlations in(e,ep)reactions and nuclear overlap functions

Abstract: A study of the effects of short-range correlations over the (e, e ′ p) reaction for low missing energy in closed shell nuclei is presented. We use correlated, quasi-hole overlap functions extracted from the asymptotic behavior of the one-body density matrix, containing central correlations of Jastrow type, up to first-order in a cluster expansion, and computed in the very high asymptotic region, up to 100 fm. The method to extract the overlap functions is checked in a simple shell model, where the exact result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Moreover, the resulting semirelativistic (SR) current is simple enough to be easily implemented in already existing nonrelativistic models of (ν l , l − ) and (ν l , l + ) reactions, where l = e or µ. It is presented here as an extension of the electromagnetic and weak-neutral current expansion originally derived in [26] and that in recent years has been widely tested and applied in several Collaborations to describe a wide variety of inclusive and exclusive electron scattering observables for intermediate energies and excitations in the vicinity of the QE peak [27][28][29][30][31][32][33][34][35][36][37]. Extensions of the SR expansion to meson-exchange currents have also been developed [38,39], and a detailed description of their application to two-body currents can be found in a recent review article [40].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the resulting semirelativistic (SR) current is simple enough to be easily implemented in already existing nonrelativistic models of (ν l , l − ) and (ν l , l + ) reactions, where l = e or µ. It is presented here as an extension of the electromagnetic and weak-neutral current expansion originally derived in [26] and that in recent years has been widely tested and applied in several Collaborations to describe a wide variety of inclusive and exclusive electron scattering observables for intermediate energies and excitations in the vicinity of the QE peak [27][28][29][30][31][32][33][34][35][36][37]. Extensions of the SR expansion to meson-exchange currents have also been developed [38,39], and a detailed description of their application to two-body currents can be found in a recent review article [40].…”
Section: Introductionmentioning
confidence: 99%
“…In this approximation there is no final-state interaction and hence the final neutron states are plane waves. The transition matrix elements appearing in the hadronic tensor (13) are computed trivially in terms of the product of a single nucleon current matrix element times the Fourier transform of a nuclear overlap function of the missing momentum, in a way which is similar to the analysis of exclusive (e, e ′ p) reactions [37] (but this time the nuclear overlap function includes the bound muon wave function). As a consequence, the exclusive hadronic tensor factorizes as the product of a single nucleon hadronic tensor times a partial momentum distribution, and the calculation is straightforward in the shell model.…”
Section: Resultsmentioning
confidence: 99%
“…Second we use the so-called semi-relativistic form of the nuclear (one-body) electromagnetic current operator, J µ (q), obtained as an expansion in powers of p/m N , the missing momentum over the nucleon mass, maintaining the exact dependence on the energy-momentum transfer. The resulting semi-relativistic DWIA model (SR-DWIA) was applied to (e, e ′ p) reactions from polarized nuclei in [25,26,36], to recoil polarization observables in [11,12], and to the unpolarized reaction in [35,39,41]. Effects beyond the impulse approximation due to meson-exchange currents (MEC) were discussed in [11,12,35] -it can be shown that they do not affect the results of the present work significantly.…”
Section: Formalism For (E E ′ P) Reactionsmentioning
confidence: 99%
“…We closely follow the pioneering work on polarization observables developed in [20,37,38]. For brevity here we just give the basic required expressions; more details about our model can be found in our previous work [11,39] and references therein.…”
Section: Formalism For (E E ′ P) Reactionsmentioning
confidence: 99%
See 1 more Smart Citation